OPTIMIZING BED OCCUPANCY RATES THROUGH SERVICE IMPROVEMENT AT BHAYANGKARA HOSPITAL, BANTEN - Yuanasari, Leddy; Suhariadi, Fendy; Fathonah; Widodo, Agung (Airlangga Development Journal, 2025)
Bhayangkara Hospital in Banten provides inpatient, outpatient, and emergency services but faces a significant challenge with a low Bed Occupancy Rate (BOR) despite adequate facilities and services. This study analyzes the factors contributing to the low BOR and develops optimization strategies through service quality improvement, focusing on five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Six operational aspects were analyzed: human resources, methods, machinery, finance, materials, and the environment. Using a qualitative approach, data were collected through in-depth interviews with hospital staff and analyzed thematically. Results highlight that limited HR competencies, especially in operating ICU and NICU units, and inadequate medical equipment are significant barriers. Strategies included intensive training with partner hospitals, budget optimization, and technology adoption (e.g., SIM RS, telemedicine). These efforts increased BOR from 60% to 75% within six months. This study underscores the critical role of HR development and service quality improvement in optimizing BOR. It offers practical recommendations for hospital administrators, including targeted HR training, resource optimization, and leveraging technology. The findings provide a framework for addressing similar challenges in other hospitals, contributing to sustainable healthcare service delivery.